2012
DOI: 10.1089/hgtb.2012.048
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-Reperfusion Increases Transfection Efficiency of Intracoronary Adenovirus Type 5 in Pig Heart In Situ

Abstract: Efficiency of intracoronary (IC) adenoviral vector transfection is impaired by the vascular endothelium. Ischemia and substances that increase vascular permeability (sodium nitroprusside, nitroglycerin) may augment adenoviral vector transfection efficiency (TE). We tested whether TE of adenoviral vector following IC infusion is improved by nitrates or by ischemia. Fluoroscopically guided angioplasty balloon catheters occluded the coronary artery in Yorkshire pigs and delivered adenoviral type 5 vector encoding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…For purely theoretical reasons, the most effective methods should deliver the vector to both the peri-ischemic regions and pre-existing collaterals. This may be accomplished by simultaneous antegrade and retrograde infusion of the adenovector 126 and also by antegrade intracoronary artery delivery if it is combined with techniques which can overcome the endothelial permeability barrier 143 (Figure 3). One of the techniques which improved antegrade adenovector delivery to the heart was proximal CA occlusion during vector delivery.…”
Section: Delivery Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For purely theoretical reasons, the most effective methods should deliver the vector to both the peri-ischemic regions and pre-existing collaterals. This may be accomplished by simultaneous antegrade and retrograde infusion of the adenovector 126 and also by antegrade intracoronary artery delivery if it is combined with techniques which can overcome the endothelial permeability barrier 143 (Figure 3). One of the techniques which improved antegrade adenovector delivery to the heart was proximal CA occlusion during vector delivery.…”
Section: Delivery Methodsmentioning
confidence: 99%
“…Both the simultaneous antegrade and retrograde delivery method and antegrade intracoronary delivery distal to an occluded angioplasty balloon, combined with coadministration of permeabilizing agents (e.g., nitroglycerin) proved to be safe and effective in pig hearts. 126,143 Since they apply conventional catheterization techniques, they may be transferable to the standard coronary catheterization practice.…”
Section: Delivery Methodsmentioning
confidence: 99%
“…5461 Catheter based percutaneous transluminal gene delivery into the coronary artery has been used in pig models to present gene therapy to ischemic myocardial tissue via retrograde delivery into the anterior cardiac vein. 59,62,63 Kaminksy et al studied the safety profile of an Ad5 vector expression the cDNA/genomic hybrid of vascular endothelial growthfactor (expressing isoforms, 121, 165 and 189) (AdVEGF-AII6A+) in an adult rat ischemia heart model to support the initiation of a clinical study to treat humans with diffuse coronary artery disease. The study concluded that the safety profile of AdVEGF-AII6A+.…”
Section: Research For Novel Therapeutic Angiogenesis Strategiesmentioning
confidence: 99%
“…Although the majority of human adults have some level of immunity against Ad5 because of prior exposure to wild-type Ad5 virus (which is the cause of common cold), preclinical studies in pigs proved that preexisting antiadenoviral immunity does not interfere with the therapeutic efficacy of Ad5FGF-4. 64 Optimizing Ad5 Vector Delivery to the Heart Current knowledge about adaptive collateral growth suggests that facilitation of both the remodeling of preexisting collaterals and of angiogenesis in the vicinity of ischemic myocardial regions may be required for therapeutic efficacy. 62 Although at very high doses, Ad5 vectors may cause inflammation, 63 neither myocardial inflammation (myocarditis) or other forms of severe inflammation have been reported among the patients treated so far with angiogenic growth factors.…”
Section: Choice Of Gene Delivery Vectorsmentioning
confidence: 99%
“…64 The method is based on earlier observations that both short-term ischemia 78 and nitric oxide donors 75 increase endothelial permeability in the heart. 64 The method is based on earlier observations that both short-term ischemia 78 and nitric oxide donors 75 increase endothelial permeability in the heart.…”
Section: Overcoming Barriers To Antegrade Intracoronary Delivery Of Amentioning
confidence: 99%